2003
DOI: 10.1902/jop.2003.74.5.590
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Treatment with an Er:YAG Laser or Scaling and Root Planing. A 2‐Year Follow‐Up Split‐Mouth Study

Abstract: It was concluded that the CAL gain obtained following non-surgical periodontal treatment with ERL or SRP can be maintained over a 2-year period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
166
5
8

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(188 citation statements)
references
References 44 publications
9
166
5
8
Order By: Relevance
“…This cause dehydration of water from bacterial cell, and finally lysis of bacterial cell wall. That is the main reason diode laser is used in non-surgical periodontal treatmen (13) . The results of this study reported that the adjunctive use of a 940nm diode laser in non-surgical periodontal treatment did not improve clinical parameters over scaling and root planning alone.…”
Section: Discussionmentioning
confidence: 99%
“…This cause dehydration of water from bacterial cell, and finally lysis of bacterial cell wall. That is the main reason diode laser is used in non-surgical periodontal treatmen (13) . The results of this study reported that the adjunctive use of a 940nm diode laser in non-surgical periodontal treatment did not improve clinical parameters over scaling and root planning alone.…”
Section: Discussionmentioning
confidence: 99%
“…So, they need to be discussed with precaution. Moreover, the literature 47 has indicated that the bactericidal effect of lasers is the main reason for their increasing application as an additional therapy to conventional periodontal treatment. In the present study, the reduced frequency of PDT or laser application than defined by the manufacturer is a possible explanation for some similar results between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies by Schwarz et al [12,13] have already demonstrated the favorable wound healing of periodontal pockets as well as the long-term stability in non-surgical Er:YAG laser pocket therapy. Additional scaling and root planning by mechanical means on the Er:YAG laser treated surface does not seem to further improve the therapeutic outcome compared to the Er:YAG laser alone [14].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the emission wavelength that is highly absorbed by water, the Er:YAG laser possesses an excellent capacity for ablating dental hard tissues, including calculus, without producing major thermal side-effects [9,10] such as carbonization, melting, or cracking of the root substance, which are usually observed following CO 2 and Nd:YAG laser irradiation [10,11]. Clinical studies have already reported the effectiveness and safety of the root surface debridement using the Er:YAG laser in non-surgical and surgical periodontal pocket therapies [12][13][14][15]. However, root surfaces following Er:YAG laser treatment in vitro exhibit a characteristic feature of micro-irregularities [16,17] and a thin affected layer stained with hematoxylin and eosin under light microscopic observation [18].…”
Section: Introductionmentioning
confidence: 99%